ANKS6 is a central component of a nephronophthisis module linking NEK8 to INVS and NPHP3 - Hoff, Sylvia (2013)
Nephronophthisis (NPH) is an autosomal recessive cystic kidney disease that leads to renal failure in childhood or adolescence. Most NPHP gene products form molecular networks. We have identified ANKS6 as a new NPHP family member that connects NEK8 (NPHP9) to INVERSIN (INVS, NPHP2) and NPHP3 to form a distinct NPHP module. ANKS6 localizes to the proximal cilium and knockdown experiments in zebrafish and Xenopus confirmed a role in renal development. Genetic screening identified six families with ANKS6 mutations and NPH, including severe cardiovascular abnormalities, liver fibrosis and situs inversus. The oxygen sensor HIF1AN (FIH) hydroxylates ANKS6 and INVS, while knockdown of Hif1an in Xenopus resembled the loss of other NPHP proteins. HIF1AN altered the composition of the ANKS6/INVS/NPHP3 module. Network analyses, uncovering additional putative NPHP-associated genes, placed ANKS6 at the center of the NPHP module, explaining the overlapping disease manifestation caused by mutations of either ANKS6, NEK8, INVS or NPHP3.